ANALISIS VEGETASI SEMAK, HERBA, DAN RUMPUT DI AREA UMBUL NILA KABUPATEN KLATEN DAN MATA AIR MUDAL KABUPATEN GUNUNGKIDUL - , FATIMATUZZAHRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Water is an important component for Life. One potential source of ground water is spring. Floor vegetation acts as a protective layer and contribute to the infiltration retention. The purpose of this study was to analyze of shrubs, herbs, and grasses vegetation around springs and study its role in the retention of water infiltration. The study was conducted in dry season between July 2013- February 2014 in Umbul Nilaâs spring, Tulung, Klaten, Central Java and Mudalâs spring, Purwosari, Gunungkidul, D.I.Yogyakarta. The simple random sampling method was used. Density, index of diversity, and index of critical value (INP), calculated for each growth form. Measurement of evapotranspiration of each growth form was done through rainwater simulation on land vegetation and bare-land. The results of floor vegetation analysis in Umbul Nilaâs spring, was obtained 8 families, 17 species of vegetation floors and 5 families with 18 species around Mudalâs spring. The results of calculation, for 3 species have the highest INP value each plot of growth form shrubs, herbs, and grasses. Growth form of shrubs in Umbul Nilaâs area: Salvia riparia 11,1%, Mimosa pudica 5,8%, and Sida rhombifolia 4,5%. Growth form of herbs: Heliotropium indicum 33,5%, Bidens pilosa 32%, Centrosema pubescens 7,5%. Growth form of grasses: Ischaemum triticeum 16,7%, Eleusine indica 11,6%, Imperata cylindrica 10,5%. Whereas in Mudal, Growth form of shrubs: Chromolaena odorata 21,4%, Flemingia macrophylla 16,9%, Triumfetta rhomboidea 7,6%. Growth form of herbs: Elephantopus scaber 27,7%, Centrosema pubescens 8,3%, Tridax procumbens 4,7%. Growth for of grasses: Ischaemum triticeum 28,6%, Paspalum conjugatum 26%, and Digitaria sanguinalis 14%. The results show that evaporation, the lowest capable of transpiration in Umbul Nila area is growth form of herbs. The lowest capable of evaporation is growth form of shurbs. Mudal, the lowest capable of transpiration is growth form of grasess and the lowest of evaporation is growth form of herbs. The results showed that infiltration retention experiment showed that the ability of water infiltration in Umbul Nila on grass-covered land was 75% is higher than the land covered with shrubs, herbs, and bare-land. While in Mudal, shrub covered by 97% compared to the land covered herbs, grasses, and bare-land.